DIFERENSIASI URIN POSITIF DAN NEGATIF MENGANDUNG METADON DENGAN ELECTRONIC NOSE BERBASIS LARIK SENSOR OKSIDA LOGAM - , NINI FIRMAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Urine samples with positive and negative contaminated methadone have been successfully identified by using electronic noses (e-nose). Two types of enose consists of 6 and 8 metal oxide gas sensor array have been employed for this identification. The negative contaminated methadone means without containing methadone. Oppositely, the positive contained methadone means sample containing methadone. The urine samples with positive contaminated methadone were collected from volunteers who have been treating methadone maintenance therapy (MMT) in local Puskesmas Gedongtengen Yogyakarta. Meanwhile, the urine samples without methadone contamination were collected from volunteers who have been consuming methadone and other drugs. Each urine sample was detected by using both types e-nose three times on different days consecutively at almost the same time (at 08.00 am local time). The feature extraction for each sensor array to respective sample was then performed by taking the peak of the response. By using principal component analysis (PCA) method, the similar patterns can be gathered in one group, while the different ones can be gathered in other groups. In this experiment, all samples are successfully separated in two groups that indicates group of urine sample with and without methadone. The total variance of PC1 and PC2 for six sensor typesof e-nose was obtained to be 99,44%, while for the eight sensors one was obtained to be 99,31%. Theresult from the repeatability testing also shows that positive contains methadone samples consistently into the respective group, as well as for negative contains methadone samples. Thus, two types e-nose are capable for differentiation between urine positive and negative contains methadone samples with high repeatibility.